Synthesis of Organotin Substituted Tricyclic Macrodiolides - Zacconi, Flavia C. (2015)
The radical addition of triorganotin hydrides, R3SnH (R=n-butyl, phenyl, neophyltin), to four unsaturated diesters of (11R,12R)-9,10-dihydro-9,10-ethaneanthracene-11,12-dimethanol leads to products of cyclohydrostannation with an average yield of around 80%. Whereas the addition of these hydrides to diacrylate and dimethacrylate leads to the expected mixtures containing two and four distereoisomeric cyclized products respectively, the addition to di-2-methyl- and di-2-phenylcinnamate yields only four out of the sixteen possible stereoisomers. The observed high stereoselectivity is consistent with a radical tandem cyclohydrostannation mechanism. Full proton (1H), carbon 13 (13C) and tin 119 (119Sn) nuclear magnetic resonance (NMR) data are given.